(untitled) (Veterinary Science, 2022)
The objective of this work was to assess the effects of phenological state, wilting and a microbial inoculant on chemical composition, organic acids concentration and ruminal degradability of dry matter (DMRD) of alfalfa silage. The pasture was cut in two phenological stages: 10 % (F10) and 50 % (F50) flowering. The material was chopped and divided into two fractions: with wilting (W) and no wilting (NW). Each fraction was sprayed with an inoculant (Lactobacillus plantarum, 5 × 109 viable cells/g, I) or with distilled water (no inoculant, NI) and ensiled in PVC microsilos, with 6 replications per treatment. After 90 days, pH, dry matter (DM), crude protein (CP), ammonia nitrogen (NH3-N), neutral detergent fiber (NDF) and acid detergent fiber (ADF), DMRD ​​at 30 h, acetic (C2), propionic (C3), butyric (C4) and lactic (LA) acids were determined. The wilting process decreased pH, NH3-N, NDF and ADF, and increased CP of the silage. In F10, wilting decreased the concentration of C2, C3 and C4, and increased LA. In F50, wilting decreased the C2 concentration at the two levels of inoculant and, only when inoculant was not applied, did wilting decrease C3 and C4, and increased LA. In F50-NW the application of inoculant decreased the content of C2, C3 and C4, and increased LA. The DMRD ​​of W was higher than NW, and it was higher in F10 vs F50 only when wilting was applied. The inoculant application decreased the NDF content and, in F50, it decreased NH3-N level. It can be concluded that the use of wilting improves the nutritional quality of alfalfa silage, while the effect of L. plantarum is limited to some combinations of treatments.